Audit Committee Membership and Competence (Literature Review) - Zalva Ananda Delfanty; Abd. Rasyid Syamsuri (Program Pascasarjana, Universitas Riau, 2026)
This study analyzes the challenges involved in enhancing the competence of audit committees as a central element of corporate governance. Competence is understood as a combination of technical knowledge, professional experience, and analytical skills that ensure effective oversight, high-quality financial reporting, and the integrity of the audit process. Through a literature review of various national and international empirical findings, the study identifies committee size, member independence, and meeting frequency as structural factors influencing audit committee capacity. However, ultimate effectiveness is determined by the professional competence of members, particularly in the fields of accounting, finance, and auditing. Regulatory compliance alone is insufficient without high-quality discussions, rigorous oversight, and adequate follow-up actions. Audit committees also face challenges such as limited technical expertise, a lack of continuous training, excessive workloads, and the absence of uniform competence standards. Furthermore, issues regarding independence, business complexity, and evolving financial reporting regulations undermine the monitoring function. Competence deficiencies result in a reduced ability to detect misstatements and fraud risks, as well as weak coordination with both internal and external auditors. The study underscores the need for capacity-building strategies—including competence-based recruitment, continuous technical training, proportional workload distribution, and enhanced governance mechanisms—to ensure independence.